The Programming of Programming: When Simulations Are Not the Right Tool - Arend, Richard J. (Academy of Management Review, 2024)
This Dialogue considers the question 'When is a simulation the right tool upon which to theorize?', using Chen et al.'s recent simulation to illustrate the issues. We define what a simulation is and what is application arena is. We then use the example to dive deeper into the challenges of the use of a simulation. Such challenges include the validity and comprehensiveness of coding assumptions, the predictability of results, and the relationships believed proven by the model. For the example, we offer alternative coding assumptions, and question why a simulation was required for their results, results neither specific to the entrepreneur or uncertainties advertised. This provides important lessons on assessing simulations, and significant points for debate about their value in analyzing particular phenomena.